2020
DOI: 10.2147/cmar.s263370
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Significance of Preoperative Gamma-Glutamyltransferase to Alkaline Phosphatase Ratio in Hepatocellular Carcinoma Patients with Curative Liver Resection: A Retrospective Cohort Study</p>

Abstract: Purpose: Gamma-glutamyltransferase (GGT) and alkaline phosphatase (ALP) were involved in the development and progression of cancers. This study aimed to evaluate the prognostic value of a preoperative GGT:ALP ratio (GAR) in hepatocellular carcinoma (HCC) patients with curative liver resection. Patients and Methods: A total of 380 HCC patients underwent curative liver resection before December 2017 and from January to December 2018 were included and stratified into training set and validation set, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“… 22 , 23 Study has also demonstrated that the GAPR was significant associated with BCLC stage, vascular invasion, and tumor size of HCC. 12 GAR was a superior prognostic factor for survival outcome than several potential prognostic indices. 34 Because these indicators are related to the occurrence and development of HCC, we select them as diagnostic indicators for APF‐NHCC.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“… 22 , 23 Study has also demonstrated that the GAPR was significant associated with BCLC stage, vascular invasion, and tumor size of HCC. 12 GAR was a superior prognostic factor for survival outcome than several potential prognostic indices. 34 Because these indicators are related to the occurrence and development of HCC, we select them as diagnostic indicators for APF‐NHCC.…”
Section: Discussionmentioning
confidence: 86%
“…The ratio of GGT to ALP can be regarded as a new prognostic factor in the clinical treatment of HCC. 12 Therefore, the ratio of GGT and ALP may serve as a useful tool for predicting the occurrence of HCC. When AAR, GAR, and GAPR were individually used for the differentiation of AFP-NHCC patients from controls, the diagnostic value of GAPR was significantly higher than that of AAR and GAR, especially in terms of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations